Studi dan Pengujian Atas Peran Monitoring Bank, Risiko, Spread Bunga Studi di BPR - Bimawan, Fitnantyo (Akademi Akuntasi Effendiharahap, 2021)
This study examined the effect of bank’s characteristic in term of monitoring power, bank risks included capital, non-performing loan, loan/deposit ratio, and bank size in term total aset on the interest rate spread, at Bank Perkreditan Rakyat ex-Karesidenan Pekalongan period of 2012 to 2014. The dependent variable was interest rate spread, which is proxy net interest margin (NIM). The independent variables were monitoring power, capital, non-performing loan, loan/deposit ratio, and total asset. Data were obtained from Laporan Keuangan Publikasi which is upload at www.BI.go.id. The analysis was used linear regression model to estimated the effect of various variables, the result of the study indicates that monitoring power was positively significant, capital was negatively significant, non-performing loan was negatively insignificant, loan/deposit ratio was negatively insignificant, and total aset was negatively significant of interest rate spread.